Translating policy transparency into policy understanding and policy support: Evidence from a survey experiment. (25th July 2017) - Porumbescu, Gregory; Bellé, Nicola; Cucciniello, Maria; Nasi, Greta
Abstract : While transparency is viewed as a means of improving citizen understanding of public policies and eliciting policy support, there are few empirical assessments of these relationships. We address this gap in the literature using an experimental design. We predict that exposure to less detailed policy information improves policy understanding, and that this effect varies according to presentation format. Further, we predict that policy understanding will correspond to greater policy support. Using a nationally representative panel of US citizens we find that exposure to detailed policy information decreases policy understanding and that the effect varies by presentation format. In addition, policy understanding is negatively associated with policy support. These findings culminate in a positive indirect effect—increasing detail reduces understanding, which in turn is negatively associated with policy support. However, interestingly, policy support was highest among those who felt they understood the policy best, yet possessed the lowest levels of actual understanding.